Micropropagation and conservation of endangered species Plantago algarbiensis and P. almogravensis - Gonçalves, Sandra (2013)
Plantago algarbiensis and P. almogravensis are endemic Al tolerant species from the Western-centre of the Algarve region (South of Portugal) and Portuguese Southwest coast, respectively, which are in risk of global extinction. The aim of this work was to establish an efficient protocol to in vitro propagate these species using shoots obtained from in vitro germinated seeds. The best results in terms of multiplication response were afforded in Murashige and Skoog’s (MS) medium supplemented with 6-benzyladenine (8.5 and 9.2 shoots per explant in P. algarbiensis and P. almogravensis, respectively). Shoots of both species showed a great rooting capacity (100 and 80 % for P. algarbiensis and P. almogravensis, respectively) that was not significantly influenced by the concentration of MS macronutrients or auxins. Plants were acclimatized to ex vitro conditions, exhibited normal development (survival rate of 95 and 80 % in P. algarbiensis and P. almogravensis, respectively), and were successfully reintroduced in their natural habitat.